Performance of carbon hydrogen storage materials as a function of post-production thermal treatment - Dohnke, E. (2012)
High-surface-area activated carbons for hydrogen storage were investigated as a function of post-synthesis surface treatment. Thermal treatment of the initial carbon in high vacuum at temperatures 200-1000 C leads to materials with significantly different surface chemistries and hydrogen storage capacities. Results from nitrogen pore-structure analyses, FT-IR spectroscopy before and after the treatment, and thermogravimetric analysis and mass spectroscopy of volatile reaction products during treatment, are reported. For treatment at 600 C, excess hydrogen adsorption at 80 K and 303 K is found to be 20-30% higher than for the untreated sample. At temperatures below 450 C, volatiles are mostly water and air; volatiles above 450 C are mostly carbon dioxide and carbon monoxide. The results are interpreted as that high-temperature treatment produces materials with a large fraction of high-binding-energy sites.